A look from the inside - Pantaleón, Dr. Arq. Carlos (Universidad Nacional del Litoral, 2019)
This work of reflection investigates the meaning of the word landscape and its value in the architectural work. It is based on the research carried out on different landscape concepts defined from the perceptual processes of man, on the imaginary ones that he forms as a product of those processes and the incidence of those imaginary in his cultural formation, and the behavior he performs in the world from the incorporation of those imaginary. In this particular case, and with the objective of reflecting on some of the notions from which a building is designed, the architectural work is considered as an intermediary between the subject that inhabits it and the environment that contains it, conceived as a device for provoke sensations through images projected by the architect. A synthesis of the history of the landscape in Occident and in Orient prefaces the work and defines the theoretical framework of this work, while exposing and documenting the concepts that are handled here. From these concepts and as a conclusion, we reflect on the contributions made by the Church in Water, designed and built by the Japanese architect Tadao Ando, ​​to this particular approach to the subject.